Methods for Researching Automated Futures. (September 2022) - Pink, Sarah
Emerging digital, automated and connected systems, devices, data, and algorithms are increasingly part of our lives. They participate in the everyday realities of participants in qualitative research and they are embedded in the infrastructures through which we research and share our scholarship, research, and practice. This article introduces this new landscape and its implications for qualitative research. I argue that we need to engage not only with questions of how automated futures are imagined by others, but with how to engage with such futures as qualitative researchers.